Landfill Leachate as A Soil Conditioner: Effects on Latosol Properties and Spinach (Amaranthus viridis) Growth: Lindi Tempat Pemrosesan Akhir Sebagai Bahan Pembenah Tanah: Dampak Terhadap Sifat Kimia Latosol Dan Pertumbuhan Bayam (Amaranthus viridis) - Lutfia Nur Indriyani; Peniwiratri, Lelanti (Jurnal Ilmu Tanah dan Air, 2025)
Leachate from the Jetis landfill in Purworejo Regency poses a risk of environmental pollution, but it also contains plant nutrients such as nitrogen, potassium, and organic matter. The purpose of this study is to ascertain how different Jetis landfill leachate concentrations affect the chemical characteristics of Latosol and assess how leachate application affects the spinach growth. A non-factorial totally randomized design was employed in this investigation with 6 treatments and 3 replicates. The treatments consisted of applying leachate at several concentrations, specifically 0% (L0), 20% (L1), 40% (L2), 60% (L3), 80% (L4), and 100% (L5). The soil was incubated with leachate for 30 days and then planted with spinach until the maximum vegetative phase. Data analysis was performed using 5% ANOVA followed by 5% DMRT test. The findings demonstrated that the application of leachate significantly raised the pH, CEC, plant height, number of leaves, wet weight, and dry weight of spinach plants. However, it had no discernible on organic-C, total-N, available-P, and available-K. The application of 20% leachate (L1) produced the highest values for plant height, number of leaves, wet weight, and dry weight of plants, which were significantly different from the control (L0). This Jetis landfill leachate is not yet effective as a fertilizer substitute, but it has the potential to be used as a soil conditioner.